Net send limits in the Lynx payment system: Usage and implications - Virgilio B. Pasin; Anna Wyllie (Bank of Canada, 2025)
In this work, we problematize the issue of the statistical visibility of the trans population in the federal government's databases and administrative records. To the extent that it is represented through informational traces or vestiges, this segment encounters problems about population recognition and the construction of citizenship, which is considered partial, precarious, or selective. Consequently, it faces obstacles in accessing public policies. As an empirical stage of the discussion, we conducted five semi-structured interviews with actors from the government and civil society who have dealt with or are dealing with the problem of absence or incompleteness of data. From the survey conducted and based on their discourses, we show that the availability and quality of information about this social segment has been a central concern, among the anxieties captured, for individuals and institutions involved in the demand for perspectives of inclusion for gender dissidences.
Keywords: C10; D82; E42; E58; G21; G41; 330; Financial institutions; Payment clearing and settlement systems; Recent economic and financial developments